Hypoglycemia-associated autonomic failure, counterregulatory responses, and therapeutic options in type 1 diabetes - Rickels, Michael R. (Ann N Y Acad Sci, 2019)
Hypoglycemia remains a major barrier to the achievement of target levels of glycemic control for most individuals with insulin-dependent type 1 diabetes (T1D). Both the loss of β cells and an accompanying defect in the α cell response to hypoglycemia predispose patients with T1D to the development of low blood glucose. Increased glucose variability, exposure to hypoglycemia, and impaired awareness of hypoglycemia all contribute to increased risk of experiencing severe hypoglycemia, which is explained by progressive impairment in epinephrine secretion and autonomic symptom generation in response to hypoglycemia leading to defective glucose counterregulation and hypoglycemia unawareness that characterize hypoglycemia-associated autonomic failure (HAAF). Interruption of HAAF requires interfering with the mechanisms of brain adaptation to low blood glucose that affect central glucose sensing and the autonomic response to hypoglycemia, or avoidance of hypoglycemia that may allow for eventual recovery of counterregulatory and autonomic symptom responses. Strategies for hypoglycemia avoidance that include continuous glucose monitoring may reduce, but do not eliminate, clinically significant hypoglycemia, with ongoing counterregulatory defects and impaired awareness of hypoglycemia. Complete avoidance of hypoglycemia can be achieved following pancreatic islet transplantation and allows for the restoration of counterregulatory and autonomic symptom responses that evidences the potential for reversing HAAF in T1D.